Current trends in heterogeneous systems: A review - Gajendra Sharma; Prashant Poudel (Trends in Computer Science and Information Technology - Peertechz Publications, 2022)
Looking at the heterogeneous system, this paper touches on the architecture of heterogeneous systems, program models, and some challenges in this field. Heterogeneous systems have become an important development trend in the current high-performance computing field. Heterogeneous systems can be seen from smartwatches, mobile phones and laptops to server systems. This paper will explore different types of heterogeneous systems such as CPU-GPU architecture, and ARM big. Little architecture. The program model for different types of heterogeneous systems where we will see how different architecture heterogeneous systems work. Then we will see some of the challenges in the heterogeneous system and finally some recommendations for future work.